Physical, Chemical and Biological Processes in Energy Geoscience - Gao, Ping; Cai, Yidong; Zhou, Yingfang; Gan, Quan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue covers the new advances in physical, chemical, and biological processes in energy geoscience, especially for unconventional gases and geothermal energy. Its major topics include (1) depositional and diagenetic processes of geo-energy reservoirs, (2) formation and evolution mechanism of pores and fractures, (3) characterization of organic and mineralogical properties of unconventional geo-energy, (4) fluid flow behaviors in porous media under geological conditions, and (5) exploration, development, and utilization of geo-energy resources (including oil, gas, and geothermal resources).